Dari Kertas ke Digital: Cetak Biru Rwanda dan Redefinisi Keaslian Akta Notaris dalam Kerangka Hukum Digital di Indonesia - Carissa Amanda Siswanto; Septhian Eka Adiyatma; Uche Nnawulezi; Jacques Kabano (Indonesia Private Law Review, 2025)
This study examines the legal recognition of electronic notarial acts in Indonesia and the regulatory inconsistencies among the Notary Law, the Electronic Information and Transactions (ITE) Law, and the Indonesian Civil Code. These inconsistencies prevent notaries from issuing authentic electronic deeds, weaken the evidentiary value of digital documents, and create legal uncertainty in electronic transactions. Using a normative juridical method with statutory, conceptual, and comparative approaches, the study analyzes Indonesia’s framework and compares it with Rwanda’s system, which expressly recognizes electronic notarial acts under Law No. 031/2016 through an integrated digital identity platform. The findings show that the physical presence requirement in the Notary Law and the exclusion of notarial deeds from electronic documents under the ITE Law are the main obstacles to electronic authentic deeds in Indonesia. The novelty of this research lies in its use of Rwanda’s regulatory model as a normative and comparative foundation for reconstructing Indonesia’s Cyber Notary framework. This study proposes revising the Notary Law and establishing a unified national digital notarial platform to strengthen the authenticity, integrity, and legal certainty of electronic deeds within Indonesia’s evolving digital legal landscape.